The influence of working capital management on the profitability of listed companies in Vietnam - Bui, Ngoc Phuong (My University, 2016)
Working capital management has become an important part in financial management because it significantly affects the performance of a company. Accordingly, numerous studies have been conducted to investigate the impacts of working capital management. Regarding the profitability, those studies indicated that efficient working capital management could enable a company to improve its profitability. In Vietnam, the relationship between working capital management and company’s profitability has been analyzed in recent years by several researchers. However, their studies only concentrated on a small number of companies. Hence, this thesis aims to deepen the relationship between working capital management and profitability by using a larger sample of Vietnamese listed companies. To be specific, the data employed in the thesis is based on a sample of 557 non-financial companies listed on the Vietnamese Stock Exchange during the period from 2009 to 2014. For the purpose of this study, Pearson correlation analysis is chosen to show the association between working capital management and a company’s profitability. Furthermore, fixed effects model and pooled ordinary least squares regressions are employed to determine how working capital management affects the profitability. The empirical results from both regressions demonstrate that Vietnamese listed companies can increase their profitability by reducing the cash conversion cycle. In addition, the elements of cash conversion cycle which are the number of days accounts receivable, the number of days inventory, and the number of days accounts payable have been examined. The results also imply that the profitability of a company can be enhanced by effectively managing each part of working capital.
Keywords: working capital management; profitability; return on assets; number of days accounts receivable; number of days accounts payable; number of days inventory; cash conversion cycle; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|